Finite-Element Simulation of Electroosmotic Mixing: A Study of the Simultaneous Effects of Working Parameters for Optimization - Reza Kalantar Feeoj; Sayed Masoud Alavi Eshkaftaki; Iman Kazemi Asfeh; Mehdi Jahangiri (International Journal of Chemical Engineering)
Micromixers are crucial parts of microfluidic systems when it comes to efficiency and precision, as mixing is the central process in most relevant applications, including medical diagnosis, chemical production, and drug discovery. In view of the importance of improving the mixing quality, for the first time, the present work investigates the simultaneous effects of mixing chamber geometry (circular, hexagonal, and octagonal), electric field frequency (5, 7, 10, and 15 Hz), inlet velocity (0.1-0.2 mm·s−1), and phase difference (0-π) on the flow inside an electroosmotic micromixer using the finite-element tool COMSOL Multiphysics 5.4 to optimize the process and achieve homogeneous mixing. The flow-field, concentration-field, and electric-field equations were coupled and solved simultaneously. The results of this research indicated that at a given inlet velocity and a specific frequency range, as frequency increases, more mixing occurs in a smaller chamber, and as the inlet velocity increases, more mixing occurs in a smaller chamber at a higher frequency. Moreover, the highest mixing level (98.16%) was obtained with a 0.1 mm·s−1 inlet velocity, 10 Hz frequency, and π/2 phase difference in a hexagonal chamber.